2004
DOI: 10.1111/j.0007-0963.2004.05871.x
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis: the development of a clinical diagnostic aid for toenail disease. Part I. Establishing discriminating historical and clinical features

Abstract: Our results have shown one historical feature and three clinical features to be strongly associated with onychomycosis. The questionnaire has been revised to include only these stems and is being tested further with the aim of achieving a binary definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 13 publications
3
27
0
4
Order By: Relevance
“…Tinea pedis has a high prevalence in the general population and has been estimated to affect up to 25% of individuals. 20,[23][24][25][26][27][28] Another finding of this study identified the frequency of occult tinea pedis as being higher in men; this is in accordance with the findings of previous studies. This implies that subjects with occult disease are able to transmit the disease despite being asymptomatic and demonstrating an absence of clinical symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Tinea pedis has a high prevalence in the general population and has been estimated to affect up to 25% of individuals. 20,[23][24][25][26][27][28] Another finding of this study identified the frequency of occult tinea pedis as being higher in men; this is in accordance with the findings of previous studies. This implies that subjects with occult disease are able to transmit the disease despite being asymptomatic and demonstrating an absence of clinical symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Fletcher et al, found that four parameters significantly related to positive mycology results were: a history of tinea pedis in the last year; scaling on one or both soles, white crumbly patches on the nail surface, and an abnormal color of the nail plate. [28] Doval et al, reported that plantar desquamation offered a positive predictive value of 81% for presence of fungi. [29] However, none of the studies professes complete reliance on clinical features alone for a diagnosis of OM.…”
Section: Diagnosismentioning
confidence: 99%
“…However, antifungal systemic therapy is expensive and may be accompanied by unwanted side effects such as drug interaction, rising liver enzymes etc. Therefore, reliable diagnostic methods are important to verify fungal infection prior treatment 3–5 …”
Section: Introductionmentioning
confidence: 99%